A fatal case of levamisole induced bone marrow failure - George, John Titus (BMJ Case Rep, 2019)
A 20-year-old college student presented with high grade, intermittent fever for 10 days associated with blood stained loose stools after taking tablet levamisole for 17 days for vitiligo vulgaris. He was febrile, had a toxic appearance and appeared pale. Investigations showed neutropaenia with thrombocytopaenia. Blood cultures were sterile and stool cultures did not grow any enteric pathogens. His bone marrow examination was suggestive of an aplastic anaemia. He was administered empirical antibiotics, granulocyte colony stimulating factor and platelet transfusions. However, his fever and blood stained stools persisted. A repeat bone marrow examination after 2 weeks still revealed a hypoplastic marrow. Hence, a diagnosis of a levamisole induced bone marrow failure was made. While being worked up for an allogeneic stem cell transplantation, he developed neutropaenic enterocolitis and refractory septic shock with carbapenem resistant Klebsiella pneumoniae and succumbed to his illness.